WOUND INFECTION IN IMMUNE COMPROMISED PATIENTS WHO WERE OPERATED IN EMERGENCY DEPARTEMENT. : JPUMHS; 2025:15:01,99 105. http://doi.org/10.46536/jpumhs/2025/15.01.602 - Ahsan Ali Lagari1, Areeba laghari2, Qunber Ali Laghari3, Nawaz Ali Dal4, Isharat Rahmeen Kaytear5 , Tufail Ahmed Baloch6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
AIM OF STUDY: To determine the wound infection in immune compromised patients who were operated in Emergency department. STUDY DESIGN: Prospective observational study. PLAC E & DURA TION: Two years’ study January 2018 to March 2020 conducted at Liaquat University of Medical and Health Sciences / Jamshoro in department of surgery PATIENTS & METHOD: The study comprises 100 patients. All were admitted from Emergency department. All patients were evaluated fully after history & clinical examinations and specific investigations pre operatively ,per operatively and post operatively (CBC) complete blood count , C reactive protein , Blood culture , urine culture, IV cannula Tip culture ,Pus culture and Sensitivity, ultra sound of abdomen, pelvis and Chest , X- ray abdomen supine and erect posture ,X Ray chest PA view ,Urine DR, Protein A/G Ratio, level of serum Albumin, Liver function Test (LFT) Serum ferritin , Lactate Dehydrogenase, Blood urea, sugar, serum electrolyte, HBSAG, HCV, & HIV, PT, APTT, INR and ECG . Typhi dot, Tuberculin test, Biopsy report and general assessment of the patients. Post operatively Contrast iv and Oral C T scan if needed RESULTS: This was a hospital based case series study of 100 patients, the maximum number of patients were in age group between 12 to 75 years. Out of 100 patients 33 patients were presented with age group between 12 to 34 year. 45 patients were presented with age group between 35 to 55 years. 22 patients were presented with age group between 54 to 75 years. Out of 100 patients, 62 were operated through mid line incisions, 25 patients were operated through right Para median incision. Out of 100 patients 10 patients were operated through Gird Iron incisions. Out of 100 patients 61 patient present with serious discharge, 25 patients with Pus discharge, 10 patients with abdominal dehiscence 4 patients presented with fecal fistula. Out of 00 patients 55 patients were presented with serum Albumin level 2 gram ,22 patients were presented Serum Albumin level 2.5 gram ,13 patients were presented Serum albumin level 3 gram ,12 patients Were presented serum Albumin level 3.3 gram Out of 100 patients 31 patient were presented hemoglobin 10 to 12 gram .44 patients were presented Hemoglobin 8 to 10 gram. 13 patients were present HBA1c 7 to 8 gram. 12 patients were presented serum creatinine. Level between 2 to 3. CONCLUSION: Patients were admitted and operated in emergency department, already immune compromised, depleted, comorbid, anemic and edematous prone to developed wound infection either superficial or deep if not treat as soon as possible patient can die systemic complications.